2019
DOI: 10.3390/cells8050509
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Hedgehog Signaling in Fibroblasts, Pancreatic, and Lung Tumor Cells by Oxy186, an Oxysterol Analogue with Drug-Like Properties

Abstract: The widespread involvement of the Hedgehog (Hh) signaling pathway in human malignancies has motivated the clinical development of Smoothened (Smo) antagonists, such as vismodegib and sonidegib. However, Smo antagonists have failed to benefit patients suffering from Hh pathway-dependent solid tumors, such as pancreatic, colorectal, or ovarian cancer. Hh-dependent cancers are often driven by activating mutations that occur downstream of Smo and directly activate the transcription factors known as glioma-associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 58 publications
(96 reference statements)
2
25
0
2
Order By: Relevance
“…Having had identified the Hh pathway inhibitory effects of Oxy16 and Oxy186 [22,23], we examined the effects of Oxy210 on Hh signaling in NIH3T3-E1 mouse fibroblastic cells treated with CAPAN-1 conditioned medium (CM) that we previously reported to contain Hh ligands [22] and found that Oxy210 robustly inhibited the mRNA expression of ligand-induced Hh target genes Gli1 and Ptch1 (Figure 4a). Oxy210 exhibited strong inhibitory effects comparable to established Gli1 inhibitors, such as HPI-1 (10 μM) and Gant61 (20 μM), with an IC 50 for inhibition of Gli1 expression of 1.83 ± 0.21 μM (Figure 4b).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Having had identified the Hh pathway inhibitory effects of Oxy16 and Oxy186 [22,23], we examined the effects of Oxy210 on Hh signaling in NIH3T3-E1 mouse fibroblastic cells treated with CAPAN-1 conditioned medium (CM) that we previously reported to contain Hh ligands [22] and found that Oxy210 robustly inhibited the mRNA expression of ligand-induced Hh target genes Gli1 and Ptch1 (Figure 4a). Oxy210 exhibited strong inhibitory effects comparable to established Gli1 inhibitors, such as HPI-1 (10 μM) and Gant61 (20 μM), with an IC 50 for inhibition of Gli1 expression of 1.83 ± 0.21 μM (Figure 4b).…”
Section: Resultsmentioning
confidence: 99%
“…NIH3T3-E1 fibroblasts were obtained from ATCC (Manassas, VA, USA) and cultured as previously described [25,26]. The human lung cancer cell lines A549 and H2030 were obtained from ATCC and cultured in RPMI-1640 medium containing 10% FBS and antibiotics as previously described [23]. CAPAN-1 human pancreatic adenocarcinoma cell line was purchased from ATCC and cultured in Dulbecco’s Modified Eagle Medium (DMEM) containing 10% FBS and antibiotics as previously described [23].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations